2020
DOI: 10.1002/adma.201907747
|View full text |Cite
|
Sign up to set email alerts
|

A ZnS/CaZnOS Heterojunction for Efficient Mechanical‐to‐Optical Energy Conversion by Conduction Band Offset

Abstract: heterojunctions have been constructed and demonstrated for controlling optical, [1] electrical, [2] mechanical [3] and magnetic characteristics. [4] In particular, semiconductor heterojunctions as the core of light-emitting diodes (LEDs) have played vital roles in electric-driven lighting and display devices. The electric potential of a semiconductor heterojunction has a strong positive effect on charge carrier transport at the interface and can tune/ control the behaviors of light emitting. [5] The advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 74 publications
2
106
0
Order By: Relevance
“…Among these, some typical oxysulfides notably enriched the color of ML emission due to its good acceptance for a large number of activators (Zhang et al, 2013 , 2015 ). It is proved that some new oxysulfide semiconductors that doped with luminescent ions, for instance, transitional metals and lanthanide ions doped CaZnOS (Huang, 2016 ; Huang et al, 2017 ; Du et al, 2019 ), SrZnOS (Chen et al, 2020 ), and BaZnOS (Li et al, 2016 ) single compounds as well as CaZnOS-ZnS heterojunctions (Peng et al, 2020 ) show novel ML performances that result in diverse applications. Meanwhile, some oxysulfides, such as Gd 2 O 2 S-based luminescent material (Büchele et al, 2015 ), has been commercialized and confirmed to be good X-ray phosphors.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, some typical oxysulfides notably enriched the color of ML emission due to its good acceptance for a large number of activators (Zhang et al, 2013 , 2015 ). It is proved that some new oxysulfide semiconductors that doped with luminescent ions, for instance, transitional metals and lanthanide ions doped CaZnOS (Huang, 2016 ; Huang et al, 2017 ; Du et al, 2019 ), SrZnOS (Chen et al, 2020 ), and BaZnOS (Li et al, 2016 ) single compounds as well as CaZnOS-ZnS heterojunctions (Peng et al, 2020 ) show novel ML performances that result in diverse applications. Meanwhile, some oxysulfides, such as Gd 2 O 2 S-based luminescent material (Büchele et al, 2015 ), has been commercialized and confirmed to be good X-ray phosphors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] In order to achieve continuous optogenetic stimulation, lanthanide‐doped CaZnOS crystals were selected as the candidate materials, which could generate sustainable ML through a piezophotonic effect, in which the photonic excitation was established by mechanically induced tribo/piezoelectric potential in the CaZnOS ( Figure a,b). [ 17 ] As an added benefit, the CaZnOS crystals can host a variety of dopants, such as manganese and lanthanides, for the delivery of tunable ML spectra (Figure 1b). The excitation energy was extracted by dopant ions in the CaZnOS host, wherein characteristic emission peaks at different wavelengths were generated (Figure 1c; Figure S1d, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in 2020, Peng et al.’s research work has reached this goal to some extent. Herein, a new class of heterojunctioned ZnS/CaZnOS piezophotonic system with remarkable ML performance in both intensity and reproducibility was demonstrated ( Figure 4 ) ( Peng et al., 2020 ). ZnS and CaZnOS were prepared by controlling the ratio of CaCO 3 and ZnS, and they accommodate Mn 2+ and lanthanide ions (such as Tm 3+ , Yb 3+ , and Pr 3+ NIR luminescent ions), respectively.…”
Section: Known Nir Mechanoluminescent Crystalsmentioning
confidence: 99%
“…
Figure 4 Scheme of proposed mechanism for mechanical-to-optical energy conversion in the piezophotonic semiconductor heterojunction Scheme of proposed mechanism for mechanical-to-optical energy conversion in the piezophotonic semiconductor heterojunction: electronic transition in the ML process is facilitated by band offsets at the heterojunction interface region (indicated by the red frame). Reproduced with permission from ( Peng et al., 2020 ). Copyright 2020 WILEY.
…”
Section: Known Nir Mechanoluminescent Crystalsmentioning
confidence: 99%